Globalization of agricultural research: Abstracts - CATIE - Centro Agronómico Tropical de Investigación y Enseñanza (CATIE, Turrialba (Costa Rica), 2014)
Guiding principles for the development of agricultural research priorities - Join science and technology strategy for tropical agricultural research